Establishing Sustainable Cell Lines of a Coral, Acropora tenuis - Kawamura, Kaz; Nishitsuji, Koki; Shoguchi, Eiichi; Fujiwara, Shigeki; Satoh, Noriyuki (Marine biotechnology (New York, N.Y.), 2021)
Planula larvae of the scleractinian coral, Acropora tenuis , consist of elongated ectodermal cells and developing inner endodermal cells. To establish in vitro cell lines for future studies of cellular and developmental potential of coral cells, larvae were successfully dissociated into single cells by treating them with a tissue dissociation solution consisting of trypsin, EDTA, and collagenase. Brown-colored cells, translucent cells, and pale blue cells were the major components of dissociated larvae. Brown-colored cells began to proliferate transiently in the culture medium that was devised for the coral, while translucent cells and pale blue cells decreased in number about 1 week after cell dissociation. In addition, when a modular protease, plasmin, was added to the cell culture medium, brown-colored cells extended pseudopodia and assumed amorphous shapes. They then continued to proliferate in clumps for more than 6 months with a doubling time of approximately 4–5 days. From 3 weeks of cell culture onward, brown-colored cells often aggregated and exhibited morphogenesis-like behavior to form flat sheets, and blastula-like clusters or gastrula-like spheres. Single cells or cell-clusters of the cell lines were analyzed by RNA-seq. This analysis showed that genes expressed in these cells in vitro were A. tenuis genes. Furthermore, each cell line expressed a specific set of genes, suggesting that their properties include gastroderm, secretory cells, undifferentiated cells, neuronal cells, and epidermis. All cell properties were maintained stably throughout successive cell cultures. These results confirm the successful establishment of a coral in vitro cell line.